Diversidade e estrutura genética em populações naturais de Cabralea canjerana (Vell.) Martius no Espírito Santo - Assis, Arícia Leone Evangelista Monteiro de (2015)
As a result of the fragmentation of the Atlantic Forest and the selective cutting process the genetic variability of tree species has become increasingly compromised. Among these tree species, the Cabralea canjerana species threatened by reduced genetic variability of their natural populations. It is necessary to the existence of more effective programs for the conservation of this species. Thus, this study aimed to characterize the genetic diversity and structure of species populations in forest remnants in two protected areas in the state of the Holy Spirit through molecular markers of type Inter Single Sequence Repeats (ISSR) and was held parallel analysis of leaf morphology, aiming to obtain the most representative variables for individuals collected in two different vegetation type. In the morphological analysis, after the removal of outliers in respect to the axis 1 (59%) in order to weight characteristics of the dry mass of the petiole (PMSF), petiole length (SL) and the weight of the dry mass of leaves (PMSF) were the most representative variables for individuals Reserve already worth for individuals Caparaó variables were weight of the dry mass of the rachis (PMSR) and leaf area (LA). These factors can be explained by genotype interactions environments. In the molecular analysis used primers 10 in 46 individuals of three different populations, yielding 73 polymorphic fragments that served as the basis for the analyzes and inter-intra-population diversity. The results indicate high levels of genetic diversity in accordance with the values of the Shannon Index, which were: Vale Reservation, 0.31, Footwear Valley, 0.44 and 0.42 Valley of Santa Marta. In the overall index analysis the value was 0.475. The AMOVA most diversity occurs within populations (73%). The correct number of groups, based on the rate of change in Ln (k), statistical ?K, indicating a convergence to three Bayesian groups (K = 3). In comparing the populations of the three populations, gene flow was 0.676, considered a low value fact that supports the formation of the three Bayesian groups and structure of the population.